Vein of Galen malformation presenting as progressive macrocephaly in a 12-month-old girl: A case report - Lindsey Cortes (SAGE Open Medical Case Reports)
Vein of Galen malformations represent about 30% of pediatric vascular abnormalities. Depending on the type, they can present insidiously with macrocephaly in the absence of other symptoms and are often misdiagnosed as benign, especially if not captured by initial imaging. The objective of this case report is to highlight this malformation to avoid incorrect diagnoses leading to a delay in proper treatment. Herein, a 12-month-old female developed progressive macrocephaly without loss of developmental milestones or focal deficits. Initial diagnostic testing with ultrasound revealed benign extra-axial fluid as the etiology at 6 months of age. With the continued progression of her macrocephaly accompanied by prominent scalp veins, magnetic resonance imaging of the brain revealed a dilated vein of Galen. The patient underwent successful cerebral embolization of a mural type vein of Galen malformation with stabilization of her head circumference by 18 months of age. This case demonstrates a clinician’s need to maintain a high index of suspicion and broad differential for children with worsening macrocephaly despite normal neurodevelopment and/or initial imaging. Recognized vein of Galen malformations are infrequently encountered in the pediatric setting as an etiology of a very common finding in infancy, macrocephaly.